Surgical management for chronic pain. Issue 8 (August 2019) - Lyons, Robert; Koneti, Kiran K.
Abstract: Chronic pain in the UK affects up to 43% of the population. The consequences include physical and psychological distress, loss of function, employment, family and social strain and increased utilization of healthcare services. Modern pain management services operate across primary, secondary and tertiary care and incorporate general practitioners, psychologists, physiotherapists, pharmacists, specialist nurses, pain physicians and surgeons. This allows for a coordinated approach to chronic pain, engaging the patient in a structured pathway from conservative measures, through to surgery if necessary. Surgical interventions have been utilized effectively throughout the 20 th century for the treatment of a variety of conditions, some of which are now effectively managed with improved pharmacological approaches or novel neuromodulation techniques. Ablative procedures that aim to permanently interrupt the pain pathway still represent the final solution for some conditions, particularly those with cancer associated pain; however, the search for less invasive, less risky measures continues. This is stimulated by an increased understanding of the neurobiology of pain transmission and the physiological changes which occur in persistent pain.